أنواع علم النحو في العربية - عبدالسلام الأسمر أ. محمد حامد (Aljameai, 2023)
المستخلص: يتكلم هذا البحث على علم النحو العربي وأنواعه في اللغة العربية، وما أنواع علم النحو التي ظهرت في عصرنا هذا بين علماء العربية، وأساتذتها، وباحثيها؟ وما أشهر المؤلفات النحوية التي وصلت إلينا؟ وما أشهر تعريفات علم النحو عند علماء العربية المتقدمين؟ وعند علماء الغرب المحدثين؟ وعند علماء اليونان؟ والعلماء اللاتينيين؟ يتضمن بحثي هذا في خاتمته مجموعة من النتائج التي توصلت إليها، تليها هوامش البحث، تليها مباشرة المصادر والمراجع مرتبة ترتيبا هجائيا، وقد تنوعت المصادر والمراجع ما بين قديمة وحديثة في موضوع بحثي هذا الذي أرجو فيه من الله العلي القدير التوفيق والنجاح والسداد، وأن يكون فاتحة خير لبقية بحوث علمية أخرى تسد القصور الذي يعتري غالبا البحوث العلمية، وما أنا إلا بشر أخطئ وأصيب، وما توفيقي إلا بالله عليه توكلت وإليه أنيب Abstract: In this research, I addressed the study of Arabic grammar and its types in the Arabic language. I started by presenting the research problem, its objectives, and its importance, and then presented the introduction of the research, which included mentioning the oldest grammatical literature that reached us from the ancient Arabic linguistic heritage, with mentioning the most famous and most prominent grammatical schools, and then mentioning the five types of grammar that the researcher will study, which are: educational grammar, specialized grammar, applied grammar, generative grammar, transformative grammar, and expressive grammar. After that, I talked about the definitions of grammar among the Arab ancient scholars, the Arab later scholars, and among the scholars of the West. At the end of this research, a set of findings was included, which I reached, followed by the margins of the research, and directly followed by a list of sources and references arranged alphabetically. A variety of old and modern sources and references were used in this research, asking the Almighty God for success. This research is the starting point for the rest of other scientific research that fills the shortcomings that often exist in scientific research, and I am only a human being who makes mistakes and right. My success can only come from Allah. In Him I trust, and unto Him I return.